De Budapest à Kaboul via Prague : l’esprit de suite de l’internationalisme socialiste - Arbour, J.-Maurice (Études internationales, 1980)
It is a well-established principle of international law that the threat or use of force against the territorial integrity or political independence of any State is forbidden. It is also recognized that every State has the sovereign and inalienable right to choose its economic System as well as its political social and cultural Systems in accordance with the will of its people, without outside interference, coercion or threat in any form whatsoever. But international law does not prohibit the use of force in the exercice of the right of self-defence if an armed attack occurs and some writers state that there is no rule of international law which forbids the government of one state from rendering assistance to the government of another state.This article is primarily concerned with legal issues related to soviet invasion of Afghanistan; its purpose is to examine official statements put forward in Moscow in order to justify the legality of this armed intervention. As will be seen, there is a perfect similarity between legal arguments used in 1956, 1968 and 1980; this is being done in order to give the domestic crisis an international colouring and to justify a demand for foreign intervention. It must be noted that Soviet troops are "not interfering" in the international affairs of Afghanistan: on the contrary, they are "fighting for" the principle of socialist self-determination of the people of Afghanistan... By definition a war conducted by the USSR is a just and defensive war...